Opini Digital Isu Kenaikan PPN 11% - Hadi, Maulana Fadia; Suratnoaji, Catur (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The issue of the 11% VAT rate increase policy being one of the issues that is widely discussed by the general public. At the beginning of April 2022 the PPN 11% keyword appeared on the trending topic Twitter which became a medium for the public to discuss the VAT increase policy by voicing their opinions regarding this issue. This research aim to mapping the communication network on the VAT increase issue using the keywords "PPN OR PPN 11%" which is then analyzed in more depth using multilevel analysis techniques from Suratnoaji & Arianto, namely: media content analysis, behavior analysis, and network analysis. Highest intensity of interactions in this issue happened on 1 April 2022 and fluctuated until 20 April 2022. There were 20509 actors and 25107 relationships formed from 9672 original tweets, 14121 retweets, 2052 quoteds and 8935 replies. The clusters formed in this network are 1698 with the largest clusters including clusters 465, 477, 315 and 279 with their respective discussions. an important aktor in the 11% VAT network, namely the account with username @alindardiantoro. This is based on the aktor's ability to disseminate information so that it has the highest centrality values. The direction of opinion formed from this network is neutral sentiment, but there is a considerable difference between negative sentiment and positive sentiment. Even though the value of positive sentiment is small, based on the clustering coefficient, cluster 279 which supports the VAT increase policy is the most compact cluster among the other largest clusters.